math

posted by .

(2w-1)^2=4(w-3)^2

Expand both sides of the equation, then simplify:

4w^1 - 4w + 1 = 4w^2 - 24w + 36
......
.....
w = 7/4

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    4(j)-7=9 Add 7 to both sides of the equation and you get 4 j = 16 Now divide both sides of the equation by 4 and you will find out what the value of j is. Whenever you perform the same mathematical operation on both sides of an equation, …
  2. MATH PLEASE CHECK IT!!2

    m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m - 5) * (m + 5)/(m - 2) = -1 (m - 2) cancels out in both the numerator and denominator on the left-hand side since you are multiplying. That leaves us with this: (m + 5)/(m - 5) …
  3. math

    Solve each formula for n. 2n = 4xp-6 3m-n=4s r/n+2=p t=100(n+3) pv/nR=T 8a+2=6b In the first example, divide both sides of the equation by 2 In the second example, add n to both sides of the equation. Try these yourself. They aren't …
  4. math

    I need help figuring out these two questions on euations with integers. -5x+20=-60 2x-3=-2 thank you so much for first: subtract 20 from both sides, simplify, then divide both sides by -5 for second: add 3 to both sides, simplify, …
  5. maths

    i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be y = 4t + 9/7 ?
  6. Find the sum of thuis question

    Can someone find the sum for this equation please. (X^2)/(X^2-16)=(5X+4)/(X^2-16) I don't think it is finding the sum, but I can simplify the equation. (X^2)/(X^2-16)=(5X+4)/(X^2-16) First, multiply both sides by X^-16. X^2 = 5X+4 …
  7. Algebra

    Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r) = [(1-r)*a]/(1-r) Simplify S*(1-r) = a Multiply terms on the left. S - S*r = a Subtract S from both sides. S-S*r - S = a - S Simplify -S*r = a - S Multiply both sides …
  8. Math

    Simplify: 24w^7t^4/6w^9t^2 And How Exactly do u do this?
  9. Math

    Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + 35 What operation solves the equation for m?
  10. Algebra

    Which of the following describes a correct method for solving the equation below?

More Similar Questions